2016
DOI: 10.5897/ajfs2016.1485
|View full text |Cite
|
Sign up to set email alerts
|

Hygienic practices and critical control points along the milk collection chains in smallholder collection and bulking enterprises in Nakuru and Nyandarua Counties, Kenya

Abstract: Dairy value chains link the actors and the activities involved in delivering milk and milk products from production to the final consumer. In every activity, the product increases in value from production, transportation, processing, packaging and storage. The study was designed to evaluate some hygienic practices along the value chain and develop the quality control system (CCPs) in the smallholder supply chain in Nakuru and Nyandarua County, Kenya. To assess the level using critical control points of complia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
1
3
1
Order By: Relevance
“…In the present study, the odds of bacterial identification from raw milk were 81% less likely among milk vendors that 7 International Journal of Food Science did not undergo testing milk for bacterial contamination as compared to those that did (p = 0 027). This finding is parallel with a study from Kenya that quality control systems aimed at the prevention of defects, rather than their detection better in the prevention of milk contamination by milk-borne pathogens [34]. Moreover, this study also showed that the odds of bacterial identification from raw milk increased by 8-fold among vendors that did not have a separate vending environment as compared to those that did (p = 0 039).…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, the odds of bacterial identification from raw milk were 81% less likely among milk vendors that 7 International Journal of Food Science did not undergo testing milk for bacterial contamination as compared to those that did (p = 0 027). This finding is parallel with a study from Kenya that quality control systems aimed at the prevention of defects, rather than their detection better in the prevention of milk contamination by milk-borne pathogens [34]. Moreover, this study also showed that the odds of bacterial identification from raw milk increased by 8-fold among vendors that did not have a separate vending environment as compared to those that did (p = 0 039).…”
Section: Discussionsupporting
confidence: 83%
“…Plastic containers adhere to milk residues making them di cult to clean compared to aluminium containers. This shows an improvement from the situation recorded in a previous study (Ndungu et al, 2016b) where 90% and 49% of farmers in Nakuru and Nyandarua counties respectively were found to be using plastic containers for transportation of milk. The improvement could have resulted from various trainings which farmers from Nakuru County received in the last years (Ndambi et al, 2019).…”
Section: Total Viable Countscontrasting
confidence: 39%
“…The improvement could have resulted from various trainings which farmers from Nakuru County received in the last years (Ndambi et al, 2019). Ndungu et al, (2016b) further observed high mean TVC: 6.455, 6.276, 6.369, and 7.138 log 10 cfu/ml from milk collected from individual cans, collection routes, milk cooler and tanker respectively in Nakuru county. This study also noted that all (100%) farmers in Nakuru often used a reusable cleaning cloth to wipe hands, equipment and udders of different cows compared to 57.7% and 80.8% of farmers in Bomet and Nyeri respectively (Table 3).…”
Section: Total Viable Countsmentioning
confidence: 89%
See 1 more Smart Citation
“…Mohamed et al [31] also reported that Salmonella spp., which can grow in improperly stored raw milk and milk products, presents a public health risk. All this only serves to confirm the five critical control points identified by Ndungu et al [32]. ese include milking at the farm level, bulking milk at collection points, transportation, and at the cooling tank.…”
Section: Discussionmentioning
confidence: 71%